Treatment of Long COVID or Post COVID syndrome: A pharmacological approach - Banerjee, Indrajit; Robinson, Jared; Sathian, Brijesh (Nepal Journal of Epidemiology, 2022)
The novel virus SARS-CoV-2 has plagued our earth for more than a quarter of a decade and is still currently a limiting factor in our daily lives. Of late a new dilemma is beginning to incapacitate a large populous who have been infected by the virus, this condition being termed as post COVID syndrome or Long COVID.Long COVID is becoming more prolific and common amongst those infected with COVID-19 and its development in patients does not delineate between those who have suffered from a symptomatic or an asymptomatic preliminary infection. The effect of this post COVID syndrome can be multisystemic in nature and can affect the daily cognitive abilities of the individual. It is therefore pertinent and of the upmost importance that therapeutic options against Long COVID are explored as the incidence of this condition is rising and will continue to do so in future. Currently no definitive treatment against Long COVID has been approved and the mainstay treatment is divided into Symptomatic, Supportive and Rehabilitative treatment with self-monitoring. The crux of the current treatment trends for Long COVID is that of a multidisciplinary approach with a great portion of the treatment implicating the patient to take an active role in their recovery, self-monitoring and treatment of the syndrome. Hyperbaric oxygen therapy as well as the use of adaptogens has shown promising results and is advisable to be added to the treatment regimen of patients to aid in decreasing fatigue in patients suffering from post-COVID syndrome. The use of melatonin in patients suffering from insomnia and poor sleep hygiene is also advisable.